Modelowanie udziału kapitału prywatnego w rozwoju infrastruktury gospodarczej - Brzozowska, Krystyna (Modelling of Private Capital Contribution into Economic Infrastructure Development, 2005)
Economic infrastructure plays a crucial role in adjustment to economic growth. Commonly the public sector is responsible for the provision of infrastructure services. In recent years interest of private capital involvement into infrastructure projects is growing. To assess the possibilities of private capital involvement three scenarios of private infrastructure projects have been prepared. The scenarios indicate that the dichotomy of public and private targets have to be balanced by certain regulative vehicles. Regulations should cover a set of provisions and legal procedures, which can create economic terms to secure social and private interests.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 11-25